INVESTIGATE THE ROLE OF TEACHER-STUDENT INTERACTION IN FOSTERING CRITICAL THINKING SKILLS AT SMP ISLAM AR-RAAFI’ - Salma; Ika Sastrawati; Hijrah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Salma, 2024 “Investigate the Role of Teacher-Student Interaction in Fostering Critical Thinking Skills at Smp Islam Ar-Raafi’”. A thesis of English Education Department Faculty of Teacher Training and Education Universitas Muhammadiyah Makassar. (Supervised by Ika Sastrawati and Hijrah). The study aims to find out whether the interaction between teachers and students can stimulate the student's critical thinking. This study examines the interaction between teachers and students. The subjects of the study were one English teacher and five students of SMP Islam Ar-Raafi’ Makassar who were selected using purposive sampling techniques. This method of research is qualitative research with phenomena experienced by the subject of research, for example interactions, learning materials, etc. This research data is collected through observation and interviews. Data analysis techniques use data reduction, data display, and conclusion/verification. This research is expected to benefit teachers and students in interacting in the classroom. In this case, teachers are asked to build interaction with students by increasing communication to students. With the interaction between teachers and students, students can exchange views, express opinions, analyze, and evaluate the materials studied, which of course can encourage the critical thinking of students. It can be concluded that the role of interaction among teacher and students is very important in fostering the student's ctirical thinking skills.